Spatial Mapping the Dengue and Chikungunya Burden in a Rural Area near Bangalore: a Descriptive Cross-Sectional Study - N R Ramesh masthi; Divya Bharathi G (Tehran University of Medical Sciences, 2024)
Background: The burden of dengue and chikungunya diseases across geographical regions of India is poorly quantified more so during Covid19 pandemic and from hospital-based studies. The objective was to assess the prevalence of dengue and chikungunya in the study area and to visualize the spatial distribution of dengue and chikungunya cases using the Quantum Geographic Information System (QGIS). Methods: This descriptive cross-sectional study was conducted among the population in villages coming under a medical college's rural field practice area near Bangalore. A total of 31 villages were selected through a simple random sampling method and 3356 subjects were surveyed through household visits. QGIS was used for spatial mapping of cases. Results: 3356 subjects were surveyed, and the prevalence of dengue and chikungunya was 1.13% and 0.02%, respectively. The overall prevalence of dengue and chikungunya cases together was 1.16%. All 39 (100%) cases had reported fever and 31 patients (79.5%) reported myalgia followed by arthralgia 22 (56.4%). QGIS supported spatial mapping of the cases and no clustering of cases was found in the study area. Conclusion: The burden of dengue and chikungunya is under reported, and the surveillance system needs to be strengthened in the rural area. Spatial mapping using QGIS may help in a better understanding of the problem. QGIS was found to be useful in the spatial mapping of the cases and there was no clustering of cases observed.